Perancangan E-Learning Berbasis Web Pada Universitas Katolik Santo Thomas - Pakpahan, Sorang; Putra, Painto Juna (LPPM UNIKA Santo Thomas Medan, 2021)
The e-learning system is absolutely necessary to anticipate the times with the support of information technology where everything is heading to the digital era, both mechanism and content. In its development, the system must be preceded by analyzing the needs of the user (user needs). In accordance with the systems and software engineering paradigm, the needs of these users are of the highest order, and are the basis for the creation and work of developers. This is all to prevent the failure of the implementation of the Wahono system, (2003). E-learning is one way to help realize the quality of good learning education. To find out how much the ability of students to receive lessons during tutoring. In addition, to unite intellectual and spiritual intelligence, it requires a good teaching and learning process system through a learning medium. By utilizing advances in technology, a tutoring information is built that can be accessed through a website.